2008
DOI: 10.1097/rct.0b013e31815896df
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Findings and Prognosis in Thymic Epithelial Tumor Patients

Abstract: Vascular obliteration and a blunt sternum-anterior mediastinum angle were predictive of thymic carcinoma. Pleural effusion and mediastinal fat infiltration were predictive of a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…Many studies have reported that TETs have characteristic computed tomography (CT) findings (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). To our knowledge, however, there has been few reports (17,19) assessing the relationship between tumor volume (TV) on CT and each subtype.…”
Section: Original Articlementioning
confidence: 99%
“…Many studies have reported that TETs have characteristic computed tomography (CT) findings (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). To our knowledge, however, there has been few reports (17,19) assessing the relationship between tumor volume (TV) on CT and each subtype.…”
Section: Original Articlementioning
confidence: 99%
“…but it cannot accurately differentiate between different subtypes of WHO classifications (11)(12)(13)(14)(15)(16)(17)(18). The importance of CT findings to distinguish early and late clinical stages has already been described (1)(2)(3)(4)16).…”
Section: Thoracic Imaging: Diffusion-weighted Mr Imaging In Thymic Epmentioning
confidence: 99%
“…CT has been thought to have a limited role in the detection of tumor invasiveness (36), even though there have been very few systematic studies comparing CT findings and thymoma invasiveness. The majority of studies assessing the thymus have included either thymic hyperplasia or thymic carcinoma, have not provided statistical analysis of the thymoma patient group alone, and have usually described these tumors with reference to the WHO classification system rather than the clinically used Masaoka-Koga staging system (37)(38)(39)(40)(41)(42). However, three new studies have compared Masaoka-Koga stage with CT findings.…”
Section: Imaging Evaluationmentioning
confidence: 99%